Analysis of Financial Reports in Measuring Performance in Sharia Banks - Fauzul Hakim Hasibuan; Listia Kumalasari; Rini Rosita Br Ritonga; Asrul Fauzan (INVOICE : JURNAL ILMU AKUNTANSI, 2023)
Analysis of a financial statement is like looking at the report cards for a company's money. It helps people inside and outside the company make decisions. By using different mathematical tools, we can understand how well the company is performing in the future and how it will perform in the future. We use a variety of ways to measure money, such as looking at how much money a company has compared to how much it owes or how much money it makes compared to how much it spends. Financial statement analysis is closely related to the field of accounting. The company's financial statements can be analyzed using several financial ratios, with the analysis of these financial statements it can be seen the condition and development of the company that has been achieved by the company in the past and when it is currently running, both private business entities and state-owned companies. The financial statements that have been analyzed can be used as an auxiliary fund for making company managerial decisions. Analysis of financial statements is basically to find out and evaluate a company's financial statements to predict the condition of the company's financial performance in the future which also aims to provide more consideration for companies with higher levels of profitability. and the level of risk.